Anisotropic optical properties of oriented silver nanorice and nanocarrots in stretched polymer films. Issue 19 (21st May 2015) - Tong, Xia; Liang, Hongyan; Liu, Yanlong; Tan, Long; Ma, Dongling; Zhao, Yue
<x xml:space="preserve">Abstract</x> Oriented arrays of silver nanorice or nanocarrots in stretched polymer films show polarization-dependent transmission of near-infrared light over a wide spectral region.